Osteoarthritis Falls Origins, Risks, and Prevention: Do we Need an Ecological Guiding Explanatory Framework? - Marks, Ray (Journal of Aging Research And Healthcare, 2026)
Lower limb osteoarthritis, a widespread age related chronic condition is often accompanied by an increased tendency to fall and thereby various degrees of intrinsic and extrinsic injury. Falls, in turn may provoke the disease alone and in turn a high falls risk and cycle of recurrent falls and heightened disability. This report which updates what is known about falls in the context of disabling osteoarthritis argues for a possible future ecological orientation rather than a focal uni dimensional approach to addressing this costly health problem. It examines osteoarthritis falls risk factors, falls injury prevention attempts, and recommendations to advance research and practice using an ecological analytic approach in this regard. Using the PUBMED data base and others, lower limb osteoarthritis linkages and falls interaction studies were sought and examined. The data revealed osteoarthritis can lead to the chances of incurring one or more falls and further health and disability challenges, while falling can provoke the onset of osteoarthritis in its own right. Although many factors appear to be involved, these are rarely viewed through a broad multi dimensional ecological perspective, thus are confusing or overwhelming to apply to the active community dwelling elderly subject.
Keywords: Aging; Ecological Model; Falls; Fall Injuries; Osteoarthritis; Prevention